TAMAN BUGAR UNTUK REMAJA DI BANJARBARU - Amelia, Rizky Noor; Wastuty, Prima Widia (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2020)
The Movement Park for Youth in Banjarbaru is a park designed as thematic park which focused at physical health that aiming to educating and to increase the youth’s interest for developing physical activity and could be an innovation for delightful destination for youth. The design of movement park is because the lack of interest and care about youth health that focusing on physical activity as a problem. The concept to solve problem is ‘Movement’ which has an aspect about physical activity those are easy, medium, and hard physical activity.